To complete the equation \(4x + 10 = x + ?\) such that it has infinite solutions, we need to make both sides of the equation equivalent for all values of \(x\).
Let's manipulate the left side of the equation:
- Start with the left side: \(4x + 10\).
- Isolate \(x\): On the right side, we already have \(x\), so we want to express everything as a multiple of \(x\).
- We can rewrite the left side: \[ 4x + 10 = x + ? \]
To equate both sides for all \(x\), we need to arrange that the coefficients match. We will isolate the term \(?\) as follows:
\[ 4x + 10 = x + (4x + 10 - x) = x + 3x + 10 \] Thus, for the equation to hold true for all \(x\), we need: \[ ? = 4x + 10 - x \] Which simplifies to: \[ ? = 3x + 10 \]
However, to express the same solution in simpler terms and maintain infinite solutions, we can assume \(? = 10\).
Thus, we can write: \[ 4x + 10 = x + 10 \] Both left and right will yield \(4x + 10 - x - 10 = 0\) or \(3x = 0\) for any \(x\).
Therefore, the value to complete the equation so that it has infinite solutions is:
\[ ? = 10 \]
So the complete equation would be \(4x + 10 = x + 10\).